THE EFFECT OF ANTI-LANGUAGE METHOD TO IMPROVE THE ABILITY OF ELEMENTARY STUDENTS OF GRADE 5 IN UNDERSTANDING THE ENGLISH GRAMMAR - Mery Silalahi; F. Ari Anggraini Sebayang (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
Studying English as a foreign language, makes learning English difficult to understand, coupled with grammar that is complicated and far different from our native language, Indonesian. The formulation patterns found in grammar usually have to be memorized by students, but most students memorize just to be able to answer questions in English lessons only. The formulation in grammar usually forms a monotonous pattern that is difficult to memorize. The activity of changing the formula contained in English grammar into words, sentences, and abbreviations that is unique and funny will form an anti-language that can be created by students in accordance with the creativity of each student. This research is an experimental study with a control and intervention group where the use of anti-language methods is carried out on a temporary intervention group in the control group, not given any treatment. Data collection using pretest and posttest was done to the intervention group and the control group. The data obtained were analyzed using univariate analysis and independent T-test. This research was also carried out using a qualitative approach, namely by examining the process of learning English that took place in class V of SD Asisi Medan in grammar material using the antilanguage method. This study produced data on apperception, exploration, discussion and explanation of concepts, as well as the development and application of the antilanguange method for grammar material in English subjects in Class V of Medan Asisi Private Elementary School. The data is generated through observations of student learning activities and teacher performance conducted during the learning of English subjects takes place. The description and summary of various conditions or situations that occur during the learning process in the classroom, then described in writing as a form of research results.